Theories of punishment at The Hague: a comment on the contributions by Alex Whiting, Harmen van der Wilt and Gerhard Werle and Aziz Epik - D'Ascoli, Silvia (Why punish perpetrators of mass atrocities?, 2021)
Silvia D’Ascoli discusses some issues that were addressed in the contributions of Whiting, van der Wilt and Werle and Epik. She agrees that the objectives and purposes of punishment guiding the sentencing process should be predetermined by the relevant system and not decided by the judges on a case-by-case basis and is disappointed how little the ICC jurisprudence on sentencing has so far contributed to the development of rationales for international punishment. Similarly, in her view it is a missed opportunity that no clear sentencing guidelines have been determined at the ICC (as was the case at the ad hoc Tribunals), including any expressed weight, from the purposes of punishment. She recalls that the initial Prosecution’s proposition of ‘80 per cent baseline’ of the statutory maximum as a starting point to determine sentences was dismissed by the Trial Chamber - and after that the Prosecution did not propose any other approach or solution.